Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Pada Sektor Barang Konsumsi di BEI - Okta Setiawan; Iwan Setiadi (Kompartemen : Jurnal Ilmiah Akuntansi, 2020)
The purpose of this study is to examine the effect of good corporate governance (GCG) on financial performance using the measurement of return on assets (ROA). The sample of this research is the manufacturing companies in the consumer goods sector which are listed on the Indonesia Stock Exchange. The data collection technique used in this study was purpose sampling, which consisted of 154 companies. The analysis of this study uses multiple linear regression analysis methods. The results showed that GCG consisting of independent commissioners had a significant positive effect on financial performance (ROA), independent audit committee had no effect on (ROA), institutional ownership had a significant positive effect on financial performance (ROA), and managerial ownership financial performance (ROA).Keywords: GCG, independent commissioner, independent audit committee, institutional ownership, managerial ownership, and financial performance.